The sponsor effect : how to be a better leader by investing in others - Hewlett, Sylvia Ann, 1946- (Harvard Business Review Press, 2019)
Who's delivering for you? Who has your back? Who's burnishing your brand and expanding what you can get done in this world? Sponsorship is a two-way alliance where a leader partners with junior talent to build their skills and advocate for their promotion--all while receiving stellar performance and loyalty in return. Many know the benefit of finding a sponsor: men and women with sponsors are much more likely to progress to the next rung in their careers than those without. But according to author Sylvia Ann Hewlett, being a sponsor is just as important to career growth as finding one. Senior executives who proactively sponsor others are 53 percent more likely to receive a promotion--and middle-level managers who have proteges are 60 percent more likely to receive a stretch assignment--than those who don't.--